Best Answer

This is a quadratic equation question which will have two answers:

2x2+42 = x2+13x

2x2-x2-13x+42 = 0

x2-13x+42 = 0

Factorising the equation gives you:

(x-6)(x-7) = 0

Therefore: x = 6 or x = 7

Q: 2x2 plus 42 equals x2 plus 13x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The expression cannot be factorised.

42 + x2 = 13x ∴ x2 - 13x + 42 = 0 ∴ (x - 6)(x - 7) = 0 ∴ x ∈ {6, 7}

42 + 42 = 84

42 and 42

28 + 42 = 70

Related questions

The expression cannot be factorised.

42 + x2 = 13x ∴ x2 - 13x + 42 = 0 ∴ (x - 6)(x - 7) = 0 ∴ x ∈ {6, 7}

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

It is (x+6)(x+7) when factored

(x - 6)(x - 7)

42 + 42 = 84

42 and 42

13 + 42 = 55

It is: 38+4 = 42

28 + 42 = 70

42

42